contestada

Sorry to bother you guys again but is it alright if u can show me how to work this question out, thanks

Sorry to bother you guys again but is it alright if u can show me how to work this question out thanks class=

Respuesta :

H4SHIM
First times both sides by m and n at the same time to get rid of the fractions. This will give you:

xn + n^2 m = xm + m^2 n

Then take x terms to one side:

xn - xm = n^2 m + m^2 n

Factorise the left hand side to get:

x(n-m) = n^2 m + m^2 n

Divide both sides by (n-m) to get x on its own and the answer:

x = (n^2 m / (n-m)) + (m^2 n / (n-m))

Hope this helps. I believe the question would’ve been asking for it to be in terms of x.


ACCESS MORE